"MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DISERTAI KUIS” : SOLUSI PENINGKATAN HASIL BELAJAR FISIKA SISWA KELAS VIII SMP - Andriswan, Andriswan; Trisna, Silvi; Yanti, Iing Rika (Jurnal Riset Fisika Edukasi dan Sains, 2019)
The involvement of students in the learning process of physics at school is not optimal. In the learning process new innovations are needed to support students to be active, one of  the application, the Teams Game Tournament (TGT) cooperative learning model can be used. This type of research is quasi experimental research, with the posttest only control group design research design. Sampling is done by cluster random sampling technique. Based on the results of data analysis, it was found that for the cognitive domain, the average for learning outcomes in the experimental class was 67.37 while the control class was 57.13. In the affective domain in the form of student activities during the learning process, it was obtained on average for the 57.43 experiment class while the control class 49.8 later, the results of hypothesis testing using two-party t test obtained t_count = 3.28 and t_table = 1.67 where 3 28> 1.67 then the hypothesis is accepted. This study shows that the learning outcomes of physics with the TGT cooperative learning model accompanied by quizzes are better than the results of students' physics learning using conventional learning in class VIII IPA Optical Instruments in SMP 28 Padang